Uranová ruda: svět, ČR a Dolní Rožinka - Císař, Luboš; Toušek, Václav, 1949-; Masarykova univerzita. Geografický ústav (2012)
Cílem této práce je představení historie a současnosti těžby uranu v České republice a ve světě. Dále tu popisuji uranová ložiska v České republice, se zaměřením na rudné pole Rožná - Olší. Na základě dostupných dat a informací o produkci uranu, o přehledu světových zásob, je porovnána a zhodnocena perspektiva těžby v jednotlivých státech a jejich podílu na celosvětové produkci uranu. V závěrečné části práce je nastíněna perspektiva těžby uranové rudy v ČR.
The aim of this theses is to present the history and the present days of uranium extraction in the Czech Republic and in the world. Further on I am trying to describe the uranium deposits in the Czech Republic with a focus on the mining field in Rožná - Olší. On the basis of the available data and information on the uranium production and awareness of the world´s reserves, it is compared and assessed the perspective of extraction in individual states and their participation in the worldwide production of uranium. In the final part of the theses, it is outlined the perspective of uranium ore extraction in the Czech Republic.
Vedoucí práce: Václav Toušek
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2012
Keywords: ložiska uranu; těžba uranu; uran; uranium deposits; uranium mining; uranium; Česko; Czechia; bakalářské práce; bachelor's theses